Groundwater Supply in Metro Manila: Distribution, Environmental and Economic Assessment - Cristina C. David; Arlene B. Inocencio; Roberto S. Clemente; Ramon P. Abracosa; Guillermo Q. Tabios (Philippine Institute for Development Studies (PIDS), 2001)
Early studies on the groundwater supply of Metro Manila have indicated inefficient resource use that could lead to the eventual decline in the groundwater level, salt water intrusion, and other similar negative externalities. Based on the preceding premise, the paper intends to present a review and assessment of how groundwater resources are developed and utilized in Metro Manila. The study has evaluated technical reports and published literature. It has also adopted water balance models as well as Long-Run Marginal Cost methodologies in calculating the groundwater potential and cost of groundwater pumping. Through these methodologies, the study requires the incorporation of environmental externalities in valuing the unit cost of groundwater extraction. Specific suggestions concerning monitoring systems, aquifer characterization, Geographic Information System application, environmental costs of groundwater pumping, and policy enforcement have been raised. The paper identifies the need to refine the methodology and data set for instituting both supply and demand relationships and projections.
Keywords: 330; natural resources and environment; water sector